Measuring the polarization of a rapidly precessing deuteron beam - Bagdasarian, Zara; Bertelli, S.; Chiladze, D.; Ciullo, G.; Dietrich, J.; Dymov, S.; Eversmann, D.; Fanourakis, G.; Gaisser, M.; Gebel, R.; Gou, B.; Guidoboni, G.; et al. (Physical review. Special topics. Accelerators and beams, 2014)
This paper describes a time-marking system that enables a measurement of the in-plane (horizontal) polarization of a 0.97−GeV/c deuteron beam circulating in the Cooler Synchrotron (COSY) at the Forschungszentrum Jülich. The clock time of each polarimeter event is used to unfold the 120-kHz spin precession and assign events to bins according to the direction of the horizontal polarization. After accumulation for one or more seconds, the down-up scattering asymmetry can be calculated for each direction and matched to a sinusoidal function whose magnitude is proportional to the horizontal polarization. This requires prior knowledge of the spin tune or polarization precession rate. An initial estimate is refined by resorting the events as the spin tune is adjusted across a narrow range and searching for the maximum polarization magnitude. The result is biased toward polarization values that are too large, in part because of statistical fluctuations but also because sinusoidal fits to even random data will produce sizable magnitudes when the phase is left free to vary. An analysis procedure is described that matches the time dependence of the horizontal polarization to templates based on emittance-driven polarization loss while correcting for the positive bias. This information will be used to study ways to extend the horizontal polarization lifetime by correcting spin tune spread using ring sextupole fields and thereby to support the feasibility of searching for an intrinsic electric dipole moment using polarized beams in a storage ring. This paper is a combined effort of the Storage Ring EDM collaboration and the JEDI collaboration.
Gesehen am 30.07.2020